First Line Family Therapy throughout the World and in India - Celikcan, Gaye (Eastern Journal of Medical Sciences, 2019)
The aim of family counseling is to regulate the emotional health of family members, to improve relationships and interactions with each other and to provide family functionalities in the functions of families. Family practice is a branch of expertise that provides continuous and multi-faceted health services to families and individuals who are responsible, and intertwined with clinical and behavioral sciences, including all age groups, both sexes, all systems and diseases. All of the primary care physicians should be able to evaluate individuals with current clinical problems and diagnosed chronic diseases, analyze with their roles within the family, provide counseling to families by examining existing psychological needs, and demonstrate a co-operative approach with family therapists when necessary.